Tuberculosis case finding in first-degree relative contacts not living with index tuberculosis cases in Kampala, Uganda - Chheng, Phalkun; Nsereko, Mary; Malone, LaShaunda L.; Okware, Brenda; Zalwango, Sarah; Joloba, Moses; Boom, Henry W.; Mupere, Ezekiel; Stein, Catherine M. (Dove Medical Press Limited, 2015)
To assess the prevalence of pulmonary tuberculosis among first-degree relative (FDR) contacts not living with tuberculosis (TB) cases. Methods: A cross-sectional analysis of household contacts living with an index TB case and FDR contacts living outside of households in Kampala, Uganda, is presented.Results: A total of 177 contacts (52 FDRs and 125 index household contacts) of 31 TB cases were examined. Compared with index household contacts, FDR contacts were older, more likely to be TB symptomatic (50% vs 33%), had a higher percentage of abnormal chest X-rays (19% vs 11%), sputum smear positive (15% vs 5%), and many similar epidemiologic risk factors, including HIV infection (13% vs 10%). Contact groups had similar pulmonary tuberculosis prevalence: 9.6% in FDR vs 10.4% in index household contacts and similar Mycobacterium tuberculosis infection: 62% in FDR vs 61% in index households.Conclusion: TB is common among FDR contacts. High TB prevalence justifies targeting FDRs during household contact investigations. Combining TB active-case finding among FDR contacts with household contact investigation in low-income setting is feasible. This should be part of national TB control program strategies for increasing TB case-detection rates and reducing community TB transmission and death.
Keywords: pulmonary tuberculosis; contact tracing